The Effect of Long - Term Computer Use on Health- Related Physiological Perspectives - Habibzadeh Nasim (International Physiology Journal, 2018)
Overusing the computer and internet can yield several health problems. The enhanced use of computer on can impact on both physiological and psychiatric health factors. It is accompanies with bad posture, musculoskeletal pains, obesity, weaker eyesight and mental illness. Health hazard of computer use life demands serious concern. Performing regular exercise largely can prevent or reduce the aforementioned issues that can be expected from computer and internet overuses. Physical activity such as 15 or 30 minutes walking for any break and reducing of the spending time to work with this kind of technology can account for as a helpful strategy toward living in more ideal manners.
Keywords: Computer